KERAGAMAN GENETIK UJI PROVENAS DAN UJI KETURUNAN araucaria cunninghamii PADA UMUR 18 BULAN DI BONDOWOSO, JAWA TIMUR - Dedi Setiadi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
A Progeny test of Araucaria cunninghamii seedling seed orchard was established comprising of eighty open–pollinated families collected from six seed source (Fak-fak, Sorong, Serui, Wamena, Manokwari and Queensland). The trial was designed as a Randomized Complete Block Design (RCBD) which comprised 80 seedlots, 4 tree- line plots with 4 replicates. At 18 months of age there were significant differences among seed sources for tree height and stem diameter. The survival rate of all seed sources was high (96.7 – 100%). Differences between families within seed source were significant both for height and diameter growth. Heritability estimates for height were moderate (h2f = 0.42, h2i = 0.19) and also for diameter (h2f = 0.57, h2i = 0.30). Genetic correlation between height and diameter was string (rg = 0.80).